Analysis of legal and technical solutions in terms of odours in Poland - Sówka, Izabela; Miller, Urszula; Karski, Leszek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
Despite solutions available in the Polish law system which could be used in conflictual situations connected with odour emission, the amount of odour complaints in Poland has been increasing. Currently applied legal solutions in Poland used in private-law and public-law ways in odour issues have been characterised. The results of analyses of available and developed technical solutions aiming to eliminate odour nuisance have been presented as well. Additionally, the results of research conducted in laboratory conditions and in chosen municipal waste management and industry facilities have been displayed. A conducted analysis pointed out the limited character of Polish legal solutions concerning odours. Therefore, the need to create an administrative and legal regulation dedicated directly to the preventing odour nuisance in Poland was emphasized. Such a regulation should include issues concerning, inter alia, emission, immision and technological standards.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 127-138
Keywords: ochrona środowiska; inżynieria środowiska